Sinophone Adaptations of Shakespeare
XV, 288 p.
Keywords: Shakespeare’s tragedies have been performed in the Sinophone world for over two centuries. Hamlet, Macbeth, and King Lear are three of the most frequently adapted plays. They have been re-imagined as political theatre, comedic parody, Chinese opera, avant-garde theatre, and experimental theatre in Hong Kong, China, and Taiwan. This ground-breaking anthology features the first English translations of seven influential adaptations from 1987 to 2007 across a number of traditional and modern performance genres in Beijing, Shanghai, Hong Kong, and Taipei. Each of the book's three sections offers a pair of two contrasting versions of each tragedy - in two distinct genres - for comparative analysis. This anthology is an indispensable tool for the teaching and research of Sinophone theatre's engagement with Western classics in the late twentieth and early twenty-first centuries. .